Sea-Level Rise and Coastal Wetlands : Impacts and Costs - Blankespoor, Brian; Dasgupta, Susmita; Laplante, Benoit (World Bank, Washington, DC, 2013)
Scientific evidence indicates that global warming could well lead to a sea-level rise of 1 meter or more in the 21st century. This paper seeks to quantify how a 1-meter sea-level rise that would affect coastal wetlands in 76 developing countries and territories, taking into account how much of wetlands would be submerged and how likely the wetlands would move inland as the coastline recedes. It is estimated that approximately 64 percent of the freshwater marsh, 66 percent of Global Lakes and Wetlands Database coastal wetlands, and 61 percent of brackish/saline wetlands are at risk. A large percentage of this loss would be shouldered by two regions: East Asia and the Pacific, and the Middle East and North Africa. At the country level, the results are extremely skewed with a small number of countries being severely affected. In East Asia, China and Vietnam would bear the brunt of these losses. In the Middle East and North Africa, Libya and Egypt would see the most losses. A rough estimate of the economic value of the goods and services produced by wetlands at risk is approximately $630 million per year in 2000 U.S. dollars.